Long-term impact of sustained-deficit irrigation on yield and fruit quality in sweet orange cv. Salustiana (SW Spain) - Garcia-Tejero, Iván; Duran zuazo, Victor Hugo; Muriel-Fernández, José Luis (Comunicata Scientiae, 2011)
Long-term impact of different sustained-deficit irrigation (SDI) treatments on a 13-year-old orange orchard (Citrus sinensis L. Osbeck, cv. Salustiana) was studied from 2004 to 2008. The experiment consisted of a control irrigation treatment which was applied at 100% of the crop evapotranspiration (ETc) values for the whole season, and three SDIs imposed as a function of different water-stress index (WSI) values, defined as the ratio of the actual volume of water supply to the ETc rate. The values defined by the WSI were 0.75, 0.65, and 0.50. The plant-water status was measured through the midday stem-water potential (ΨStem). Yearly, yield and fruit quality were evaluated at harvest in each treatment, and a global analysis was carried out using the whole dataset. Overall, no significant differences were found in fruit yield between SDIs and control treatments, although significant differences appeared in some of the fruit-quality parameters (total soluble solids and titrable acidity) which also showed significant relationships with integrated stem-water potential (ΨInt) and irrigation water applied. These findings lead us to conclude that SDIs have important and statistically significant effects on fruit quality. Thus, the application of sustained-deficit irrigation (SDI with WSI of 50) provides promising possibilities for optimising citrus irrigation and boosting the water productivity for citrus orchards in a semiarid Mediterranean climate.